A conformational transition of the D′D3 domain primes von Willebrand factor for multimerization - Gruber, Sophia; Löf, Achim; Hausch, Adina; Kutzki, Fabian; Jöhr, Res; Obser, Tobias; König, Gesa; Schneppenheim, Reinhard; Aponte-Santamaria, Camilo; Gräter, Frauke; Brehm, Maria A.; Benoit, Martin; et al. (Blood advances, 2022)
Von Willebrand factor (VWF) is a multimeric plasma glycoprotein that is critically involved in hemostasis. Biosynthesis of long VWF concatemers in the endoplasmic reticulum and the trans-Golgi is still not fully understood. We use the single-molecule force spectroscopy technique magnetic tweezers to analyze a previously hypothesized conformational change in the D′D3 domain crucial for VWF multimerization. We find that the interface formed by submodules C8-3, TIL3, and E3 wrapping around VWD3 can open and expose 2 buried cysteines, Cys1099 and Cys1142, that are vital for multimerization. By characterizing the conformational change at varying levels of force, we can quantify the kinetics of the transition and stability of the interface. We find a pronounced destabilization of the interface on lowering the pH from 7.4 to 6.2 and 5.5. This is consistent with initiation of the conformational change that enables VWF multimerization at the D′D3 domain by a decrease in pH in the trans-Golgi network and Weibel-Palade bodies. Furthermore, we find a stabilization of the interface in the presence of coagulation factor VIII, providing evidence for a previously hypothesized binding site in submodule C8-3. Our findings highlight the critical role of the D′D3 domain in VWF biosynthesis and function, and we anticipate our methodology to be applicable to study other, similar conformational changes in VWF and beyond.
Gesehen am 12.01.2023